Physiological responses in elite junior triathletes during field testing - Gibbons, T. P.; Mulligan, S. E.; Wilber, R. L.; Kearney, J. T. (Medicine & Science in Sports & Exercise, 1996)
Junior triathletes (M = 8; F = 8) participated in field testing of the sport's three activities. The following were found. 1. Heart rate (HR) was significantly higher during running than in cycling. 2. Females elicited similar lactate levels (HLa) in all activities whereas males were significantly higher in swimming and cycling than in running. 3. Ratings of perceived exertion (RPE) for running and swimming were comparable in both males and females but less in cycling. Implication. To truly understand the responses of triathletes it is necessary to independently assess parameters in each activity. HR, HLa, and RPE should not be considered to be similar across all activities or of a similar response nature between the sexes.